The original Lujan syndrome family has a novel missense mutation (p.N1007S) in the MED12 gene. Issue 7 (16th March 2007) - Schwartz, Charles E; Tarpey, Patrick S; Lubs, Herbert A; Verloes, Alain; May, Melanie M; Risheg, Hiba; Friez, Michael J; Futreal, P Andrew; Edkins, Sarah; Teague, Jon; Briault, Sylvain; Skinner, Cindy; et al.
Abstract : A novel missense mutation in the mediator of RNA polymerase II transcription subunit 12 ( MED12 ) gene has been found in the original family with Lujan syndrome and in a second family (K9359) that was initially considered to have Opitz–Kaveggia (FG) syndrome. A different missense mutation in the MED12 gene has been reported previously in the original family with FG syndrome and in five other families with compatible clinical findings. Neither sequence alteration has been found in over 1400 control X chromosomes. Lujan (Lujan–Fryns) syndrome is characterised by tall stature with asthenic habitus, macrocephaly, a tall narrow face, maxillary hypoplasia, a high narrow palate with dental crowding, a small or receding chin, long hands with hyperextensible digits, hypernasal speech, hypotonia, mild-to-moderate mental retardation, behavioural aberrations and dysgenesis of the corpus callosum. Although Lujan syndrome has not been previously considered to be in the differential diagnosis of FG syndrome, there are some overlapping clinical manifestations. Specifically, these are dysgenesis of the corpus callosum, macrocephaly/relative macrocephaly, a tall forehead, hypotonia, mental retardation and behavioural disturbances. Thus, it seems that these two X-linked mental retardation syndromes are allelic, with mutations in the MED12 gene.